Discussing The Problems Of Implementing Iddah For Career Women - Nur Solikin; Amran Khaliqurrahman (Activa Yuris: Jurnal Hukum, 2021)
Every human being expects a lasting relationship with his partner, but often relationships fail either because of divorce or death. The failure of a husband and wife relationship has a legal impact on a wife who is left behind, the wife who is left behind is obliged to perform iddah, iddah is Islamic law which aims to ensure that a woman's womb is empty before remarrying another man. In the implementation of iddah, there are restrictions to do, including the prohibition of applying, marrying, leaving the house and ihdad. Ihdad is a prohibition on dressing up. This problem then becomes a problem in itself for a career woman who in her daily life is required to leave the house to carry out her activities in her role as a career woman. As a professional, career women are required to dress and look like a pro. This then becomes a problem for a career woman who is carrying out iddah. On the one hand, make-up is prohibited, on the other hand, they are required to do so. Basically, Wahbah Zuhaili mentions that the essence of ihdad is to break the path that can make other prohibitions done, namely the interest of people to propose and get married. From the essence of the ihdad, a pregnant woman can take a middle path, which is to continue to carry out her role as a career woman, and keep her behavior and style simple so as not to invite men to approach and propose to her. That way iddah as sharia and the essence of ihdad can still be carried out.